(untitled) (Research, Society and Development, 2023)
Introduction: Benign prostatic hyperplasia affects men over 45 years after the appearance of urinary symptoms with a negative impact on quality of life, requiring a surgical approach. Objective: to comparatively evaluate postoperative complications in patients undergoing Transurethral Resection of the Prostate and Holmium Laser Prostatic Enucleation in a university hospital. Method: quantitative, descriptive, retrospective, documentary study with analysis of medical records of patients undergoing TURP and HoLEP, from September 2021 to March 2022. Postoperative complications were classified based on the Clavien Dindo Classification. Data were tabulated and analyzed using the IBM Statistical Package for the Social Sciences version 29.0 program, using Student’s t test and Fisher’s exact test to compare samples. The significance level used was 5%. The project was approved by the Research Ethics Committee. Results: 61 medical records were eligible for the study, 35 for RTup and 26 for the HoLEP technique. Mean length of stay, use of intermittent urinary catheterization postoperatively, prostate weight and pain were significantly lower in HoLEP (p < 0.05). The frequencies of urinary retention and bleeding were higher in the TURP technique. Hypoglycemia, urinary incontinence, nausea and vomiting and acute confusion were not statistically significant (p > 0.05) with reduced occurrences in the patients studied. Conclusion: The results allowed the comparison between the two surgical techniques in relation to postoperative complications, allowing nursing interventions capable of increasing the quality of care.